RENARRATING THE ISLAMISATION OF THE MALAY-INDONESIAN ARCHIPELAGO IN 13th-19th CENTURIES - Safari, Safari; Amrulloh, Muhammad Afif; Musadad, Asep Nahrul (Islam Futura, 2024)
This article aims at re-presenting the Islamisation of the Malay-Indonesian archipelago from the 13th to 19th century, focusing on the narrative of intellectualism and activism conducted inter-relatedly during the very act of religious proselytization. The background of this research arises from the need to understand the complexity of Islamisation in the archipelago, on the one hand, and the negligence of such narrative in the historiography of islamization, on the other. Taking this as the basis of narrative, this article will re-explain the major phases in the Islamization of the archipelago by paying attention both to the political variable and, particularly, the intellectual-historical aspects. This paper uses the historical-descriptive method by collecting and analyzing relevant historical materials. The selected data will be re-narrated within the framework of intellectualism and activism in the Islamization process. This research also uses the comparative method to compare the phases of Islamization in various regions of the archipelago, thus providing a more complete picture of the dynamics that occurred in the 13th to 19th centuries. The expected purpose is to go beyond the political-historical perspective that currently dominates the historiography of Islamization and marginalizes the proselytizing aspect which is an intertwining of intellectualism and activism in that process.